Forgotten Actors: Glycoside Hydrolases During Elongation Growth of Maize Primary Root - Nazipova, Alsu; Gorshkov, Oleg; Eneyskaya, Elena; Petrova, Natalia; Kulminskaya, Anna; Gorshkova, Tatyana; Kozlova, Liudmila (Frontiers in Plant Science, 2022)
Plant cell enlargement is coupled to dynamic changes in cell wall composition and properties. Such rearrangements are provided, besides the differential synthesis of individual cell wall components, by enzymes that modify polysaccharides in muro. To reveal enzymes that may contribute to these modifications and relate them to stages of elongation growth in grasses, we carried out a transcriptomic study of five zones of the primary maize root. In the initiation of elongation, significant changes occur with xyloglucan: once synthesized in the meristem, it can be linked to other polysaccharides through the action of hetero-specific xyloglucan endotransglycosidases, whose expression boosts at this stage. Later, genes for xyloglucan hydrolases are upregulated. Two different sets of enzymes capable of modifying glucuronoarabinoxylans, mainly bifunctional α-arabinofuranosidases/β-xylosidases and β-xylanases, are expressed in the maize root to treat the xylans of primary and secondary cell walls, respectively. The first set is highly pronounced in the stage of active elongation, while the second is at elongation termination. Genes encoding several glycoside hydrolases that are able to degrade mixed-linkage glucan are downregulated specifically at the active elongation. It indicates the significance of mixed-linkage glucans for the cell elongation process. The possibility that many glycoside hydrolases act as transglycosylases in muro is discussed.